Polyelectrolytes in Hot Melt Extrusion: A Combined Solvent-Based and Interacting Additive Technique for Solid Dispersions - Felix Ditzinger; Catherine Dejoie; Dubravka Sisak Jung; Martin Kuentz (MDPI AG, 2019)
Solid dispersions are important supersaturating formulations to orally deliver poorly water-soluble drugs. A most important process technique is hot melt extrusion but process requirements limit the choice of suitable polymers. One way around this limitation is to synthesize new polymers. However, their disadvantage is that they require toxicological qualification and present regulatory hurdles for their market authorization. Therefore, this study follows an alternative approach, where new polymeric matrices are created by combining a known polymer, small molecular additives, and an initial solvent-based process step. The polyelectrolyte, carboxymethylcellulose sodium (NaCMC), was tested in combination with different additives such as amino acids, meglumine, trometamol, and urea. It was possible to obtain a new polyelectrolyte matrix that was viable for manufacturing by hot melt extrusion. The amount of additives had to be carefully tuned to obtain an amorphous polymer matrix. This was achieved by probing the matrix using several analytical techniques, such as Fourier transform infrared spectroscopy, differential scanning calorimetry, hot stage microscopy, and X-ray powder diffraction. Next, the obtained matrices had to be examined to ensure the homogeneous distribution of the components and the possible residual crystallinity. As this analysis requires probing a sample on several points and relies on high quality data, X-ray diffraction and starring techniques at a synchrotron source had to be used. Particularly promising with NaCMC was the addition of lysine as well as meglumine. Further research is needed to harness the novel matrix with drugs in amorphous formulations.